Potencial de comércio brasileiro com seus principais parceiros: uma análise com o modelo gravitacional - Tartas, Rubiele Liandra (Universidade do Vale do Rio dos Sinos, 2016)
The integration of a country in international trade is a determining factor for their economic potential. An open economy is able to provide development by improving the population's quality of life and generate economic growth from improved allocative efficiency and technological diffusion. While international trade is important for most countries, Brazil is an exception, with a small trade-to-GDP ratio near to 20%. Considering these findings, this study analyses whether Brazilian trade with its 10 major trading partners already reached its potential or whether there still space to increase. It uses a panel data gravity model, with fixed effects, to estimate Brazilian potential bilateral trade with 68 countries in the period 2001-2014. The results show that actual and potential trade is quite similar, with a small difference of 2% in 2014, but it also was possible to note that in some important trading partners of Brazil, especially United States, Germany and Japan, there is room from increasing trade relations.
Keywords: Fluxo bilateral de comércio; Modelo gravitacional; Brasil; Flow bilateral trade; Gravity model; Brazil; ACCNPQ::Ciências Sociais Aplicadas::Economia